Factors Affecting Accounting Students In Choosing Accounting Career Path - Raharja, Surya; Liany, Dewi (Jurnal Dinamika Akuntansi, 2020)
This study aims to empirically examine factors that influence accounting students in choosing their career path. The samples were 181 students from six biggest universities in Semarang, Indonesia. In this study, data were collected using questionnaire survey and analyzed using multiple linear regression. The results of this study indicate that intrinsic motivation, extrinsic motivation, career exposure, and social values influence the career paths accounting student. While third parties positively influence accounting students in determining career path but it is not statistically significant. These findings may help us to understand how to improve career path among accounting students